STUDY ON DISCHARGE HEAT UTILIZATION OF 250 MWe PCMSR TURBINE SYSTEM FOR DESALINATION USING MODIFIED MED - Andang Widiharto; Atinna Paramita Gunawan (JURNAL TEKNOLOGI REAKTOR NUKLIR TRI DASA MEGA, 2013)
PCMSR (Passive Compact Molten Salt Reactor) is one type of Advanced Nuclear Reactors. The PCMSR has benefit charasteristics of very efficient fuel use, high safety charecteristic as well as high thermodinamics efficiency. This is due to its breeding capability, inherently safe characteristic and totally passive safety system. The PCMSR design consists of three module, i.e. reactor module, turbine module and fuel management module. Analysis in performed by parametric calculation of the turbine system to calculate the turbine system efficiency and the hat available for desalination. After that the mass and energi balance of desalination process are calculated to calculate the amount of distillate produced and the amount of feed sea water needed. The turbine module is designed to be operated at maximum temperature cycle of 1373 K (1200 0C) and minimum temperature cycle of 333 K (60 0K). The parametric calculation shows that the optimum turbine pressure ratio is 4.3 that gives the conversion efficiency of 56 % for 4 stages turbine and 4 stages compressor and equiped with recuperator. In this optimum condition, the 250 MWe PCMSR turbine system produces 196 MWth of waste heat with the temperature of cooling fluid in the range from 327 K (54 0C) to 368 K (92 0C). This waste heat can be utilized for desalination. By using MMED desalination system, this waste heat can be used to produce fresh water (distillate) from sea water feed. The amount of the destillate produced is 48663 ton per day by using 15 distillation effects. The performance ratio value is 2.8727 kg/MJ by using 15 distillation effects.Keywords: PCMSR, discharged heat, MMED desalination PCMSR (Passive Compact Molten Salt Reactor) merupakan salah satu tipe dari Reaktor Nuklir Maju. PCMSR memiliki keuntungan berupa penggunaan bahan bakar yang sangat efisisien, sifat keselamatan tinggi dan sekaligus efisiensi termodinamika yang tinggi. Hal ini disebabkan oleh kemampuan pembiakan bahan bakar, sifat keselamatan melekat serta sistem keselamatan yang secara total bersifat pasif. Desain PCMSR terdiri dari tiga modul, yaitu modul reaktor, modul turbin dan modul pengelolaan bahan bakar. Analisis dilakukan dengan melakukan perhitungan parametrik sistem turbin untuk menghitung efisiensi sistem turbin dan kalor yang tersedia bagi desalinasi. Selanjutnya dilakukan perhitungan neraca massa dan neraca energi proses desalinasi untuk menghitung jumlah distilat yang dihasilkan serta umpan air laut yang dibutuhkan. Modul turbin PCMSR dirancang untuk dapat dioperasikan pada suhu siklus maksimum 1373 K (1200 0C) dan suhu siklus minimum 333 K (60 0K). Perhitungan parametrik menunjukkan bahwa perbandingan tekanan turbin yang optimum adalah 4,3 dan memberikan efisiensi maksimum sebesar 56 % dengan menggunakan 4 tingkat turbin serta 4 tingkat kompresor yang dilengkapi dengan rekuperator. Pada kondisi optimum ini, turbin PCMSR dengan daya keluaran 250 MWe menghasilkan kalor sisa sebesar 196 MWth dengan suhu fluida pendingin berkisar dari 327 K (54 0C) hingga 368 K (95 0C). Kalor sisa ini dapat digunakan untuk memproduksi air tawar dengan cara desalinasi air laut. Dengan menggunakan sistem desalinasi MMED, jumlah destilat yang dapat dihasilkan adalah 48663 ton per hari dengan menggunakan 15 efek destilasi. Nilai rasio performansi adalah 2,8722 dengan menggunakan 15 efek destilasi. Kata kunci: PCMSR, kalor sisa, MMED desalinasi